Economic feasibility of growing sorghum as a bioenergy crop - Estes, Michelle E. (Kansas State University, 2014)
The purpose of this research is to evaluate and gain a better understanding of the economic feasibility of Kansas farmers growing energy sorghum for biofuel production. The net returns for 11 crop systems that included a no-till or reduced-till option and the rotations involved wheat, grain sorghum, dual-purpose sorghum, and photoperiod sensitive sorghum were simulated in SIMETAR© developed by Richardson, Shumann, and Feldman (2004) using historical data on yields and prices. The price and yield data originates from an agronomic study conducted in Hesston, KS. The biomass yields for the 3 varieties of sorghum are based on experimental work performed in Manhattan, KS. The sorghum biomass prices were obtained from the United States Department of Agriculture Agricultural Marketing Service. Costs for the crop systems are based on the 2014 Kansas State University Herbicide handbook (Thompson et al. 2014), Dhuyvetter, O’Brien, and Tonsor (2014), and Dhuyvetter (2014). The net returns were simulated under five contract scenarios including: a Spot Market contract, a Minimum Price contract, a BCAP Price contract, and 2 levels of the Gross Revenue Guarantee contracts – 60% and 100%. Risk analysis was performed on the simulated net returns through use of the Excel add-in SIMETAR©. Stochastic efficiency analysis was used to evaluate the systems based on the distribution of net returns and risk preferences. The findings are summarized around three important factors influencing farmers’ economic feasibility of growing sorghum for biofuel use: crop systems, risk preferences, and contract specification. Results indicate that the no-till wheat and dual-purpose sorghum crop system without biomass production has the lowest costs and the no-till wheat and photoperiod sensitive sorghum system has the highest production cost. The crop systems that have a no-till option allow for the highest grain and biomass yields. Also, crop systems rotated with wheat are more preferred among producers due to higher net returns. The NTWDPS With system under the BCAP Price contract has the highest net returns and is highest in preference. The findings indicate that the risk aversion does affect the decision to produce sorghum for biofuel, but the effect is not very significant. In terms of contract specification, the results indicate that for Kansas producers, the BCAP Price contract will offer the highest net returns. These findings contribute additional insight on factors affecting Kansas farmers’ economic feasibility of producing sorghum for biofuel and can have important implications for biofuel industry actors and policy makers.
Keywords: Bioenergy; Sorghum; Kansas; Risk Preferences; Contracts; Economics, Agricultural (0503)